Tracing origins of uranium ore concentrates (UOCs) by multidimensional statistical analysis of rare-earth impurities1. Issue 2 (28th February 2015) - Lin, Mu; Zhao, Yonggang; Zhao, Lifei; Li, Lili; Wang, Fan; Zhu, Liuchao; Hu, Xiaonan; Ning, Wei
<x xml:space="preserve">Abstract</x> A novel approach using REE data of uranium ores instead of UOC samples to trace the origins of unknown UOCs was developed.